Synthesis of 1-perfluoroalkyl-3-heteroaryl bicyclo[1.1.1]pentanes via visible light-induced and metal-free perfluoroalkylation of [1.1.1]propellane. Issue 5 (13th February 2023) - Yan, Boan; Xu, Gongcheng; Han, Hang; Hong, Jun; Xu, Wenhao; Lan, Deyou; Yu, Chuanming; Jiang, Xinpeng
Abstract : Visible light-induced perfluoroalkylation of [1.1.1]propellane provides a sustainable way to incorporate perfluoroalkyl-substituted BCPs into various heterocycles. Abstract : Perfluoroalkyl groups containing bicyclo[1.1.1]pentanes (BCPs) are gaining increasing interest in the pharmaceutical industry and materials science; however, the development of an efficient methodology to construct perfluoroalkylated BCPs remains a challenging task. In this paper, we present a metal-free strategy to synthesize 1-perfluoroalkyl-3-heteroaryl bicyclo[1.1.1]pentanes using an electron donor–acceptor (EDA) complex for the perfluoroalkylation of [1.1.1]propellane. After visible light irradiation, the resulting EDA complexes formed by perfluoroalkyl iodide and DBU lead to the generation of perfluoroalkyl radicals. These then sequentially react with highly strained [1.1.1]propellane and various heterocyclic compounds. Mechanistic studies revealed that this method proceeded via a radical chain reaction. This strategy may provide a versatile and sustainable way to obtain 1-perfluoroalkyl-3-heteroaryl bicyclo[1.1.1]pentanes with good functional group tolerance under mild conditions.